The Analysis of Factors Affecting Dividend Policy in Food and Beverage Sector Manufacturing Companies Listed in Indonesia Stock Exchange in 2015-2017 - Nia Angelia; Nagian Toni (Budapest International Research and Critics University, 2020)
Dividend policy is one of the policies in the company that must be considered and considered carefully. The dividend policy determines the amount of profit allocation that can be distributed to shareholders (dividends) and the profit allocation that a company can hold. The greater the retained earnings, the smaller the profits that will be distributed to shareholders. In the allocation of profits, various kinds of problems are encountered. Dividends are considered as a way to reduce the problems that arise between management and shareholders by giving the rights of shareholders. There are several factors that influence dividend policy, but researchers only examine three variables, namely liquidity, profitability and leverage. This study aims to examine the effect of variable liquidity, profitability and leverage on dividend policy both partially and simultaneously. The sample of this study is the food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017 with a total of 25 companies using a purposive sampling method obtained as many as 18 sample companies. The analytical method used is the classic assumption test and hypothesis testing and multiple linear analyses. The results showed that simultaneously all independent variables influence dividend policy. Profitability partially affects dividend policy while liquidity and leases partially do not affect dividend policy. The adjusted R square value of 0.382 indicates the dependent variable (Dividend Payout Ratio) can be explained by the independent variables (liquidity, profitability and leverage) of 38.2%.